2017
DOI: 10.4314/njp.v44i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of bacteraemia among HIV-infected under -five children in a tertiary hospital in Kano, Nigeria

Abstract: Abstract:Background: Bacterae-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Salmonella isolation in this study was low and was in older children and young adults. This is similar to studies from Kano [69], Uyo [71] and Ilorin [92] but in contrast to reports from North central and North western Nigeria where only children 5 years and below where studied [17]. Salmonella BSI was high in studies in children with protein energy malnutrition [43], Sickle Cell Disease [44] and HIV [69] in Nigeria.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Salmonella isolation in this study was low and was in older children and young adults. This is similar to studies from Kano [69], Uyo [71] and Ilorin [92] but in contrast to reports from North central and North western Nigeria where only children 5 years and below where studied [17]. Salmonella BSI was high in studies in children with protein energy malnutrition [43], Sickle Cell Disease [44] and HIV [69] in Nigeria.…”
Section: Discussionsupporting
confidence: 83%
“…This is similar to studies from Kano [69], Uyo [71] and Ilorin [92] but in contrast to reports from North central and North western Nigeria where only children 5 years and below where studied [17]. Salmonella BSI was high in studies in children with protein energy malnutrition [43], Sickle Cell Disease [44] and HIV [69] in Nigeria. In a population based, multi-country Ty-phoid fever Surveillance in Africa Programme [93] in which Nigeria was not included, the most frequent non-contaminant bacteria isolated were S. typhi 24%, Non-Typhoidal Salmonella 17%, S. aureus 12%, E. coli 8%, and Streptococcus pneumoniae.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…[ 6 , 7 ] Data obtained from a study in African countries showed that the median prevalence of resistance to oxacillin (an antibiotic used in laboratories to test for meticillin resistance) in S. aureus isolated from febrile patients was 13.4% for West Africa and 8.0% for East Africa [ 6 ]. In hospitalised children living with HIV (CLWH) who have bloodstream infections in Kano, S. aureus accounted for 4/19 (21%) of the isolates [ 8 ]. All four isolates were resistant to oxacillin [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In hospitalised children living with HIV (CLWH) who have bloodstream infections in Kano, S. aureus accounted for 4/19 (21%) of the isolates [ 8 ]. All four isolates were resistant to oxacillin [ 8 ].…”
Section: Introductionmentioning
confidence: 99%